Phenotypic Characterization, Genetic Diversity Assessment in 6,778 Accessions of Barley (Hordeum vulgare L. ssp. vulgare) Germplasm Conserved in National Genebank of India and Development of a Core Set - Kaur, Vikender; Aravind, J.; Manju,; Jacob, Sherry R.; Kumari, Jyoti; Panwar, Bhopal S.; Pal, Narendra; Rana, Jai C.; Pandey, Anjula; Kumar, Ashok (Frontiers in Plant Science, 2022)
Entire collection of cultivated barley germplasm accessions conserved in Indian National Genebank (INGB) was characterised for 9 qualitative and 8 quantitative traits to assess the nature and magnitude of prevailing genetic variability and to develop a core set. Wide range of variability was observed for days to spike emergence (51–139 days), days to physiological maturity (100–152 days), plant height (45.96 cm–171.32 cm), spike length (3.44–13.73 cm), grain number/spike (10.48–82.35) and 100-grain weight (1.20–6.86 g). Initially, seven independent core sets were derived using 3 core construction tools– MSTRAT, PowerCore and Core Hunter 3 (CH3) by employing maximisation method, heuristic sampling and optimisation of average genetic distances, respectively. The core set generated by CH3 by simultaneous optimization of diversity and representativeness, captured maximum genetic diversity of whole collection as evident from desirable genetic distance, variance difference percentage (VD; 87.5%), coincidence rate of range (CR; 94.27%) and variable rate of coefficient of variance (VR; 113.8%), which were more than threshold value of VD (80%), CR (80%) and VR (100%) required for good core collection. The coefficient of variation and Shannon–Weaver diversity indices were increased in the core set as compared with whole collection. The low value of Kullback-Leibler distance (0.024 to 0.071) for all traits and quantile-quantile plots revealed negligible difference between trait distribution pattern among the core set and entire assembly. Correlogram revealed that trait associations and their magnitude were conserved for most of the traits after sampling of core set. The extraction of INGB barley core set and identification of promising accessions for agronomically important traits in different genetic backgrounds will pave the way for expedited access to genetically diverse and agronomically important germplasm for barley breeding.